Thinking in the Context of Urban Women’s Rights: A Review into the European Union and Turkey - Kutlu, Salih Ziya; Saygın, Didem; Erdem, Asime Dilara (Journal of Applied And Theoretical Social Sciences, 2024)
The concept of urban resilience or urban resilience in literature; although it is often considered in the area of climate change or natural disasters, it also has economic, social and cultural dimensions. It is therefore necessary to consider the city as a whole and also consider the social and economic situations, quality of life and spatial areas of the people living in the city in the context of urban resilience. It is highlighted that disadvantaged groups living in cities are more affected by shocks experienced by the city, taking into account that urban resilience cannot be kept separate from social risks. Women, who make up half of society, are thought to feel urban shocks and urban poverty more. So the question of the research is does increasing women’s participation in economic life increase their urban resilience? To survive these risks with minimal damage, women's education levels need to be improved, their employment increased. in the EU with EUROSTAT data; the TUIK data assessed the position of women in Turkey and the possibility of building urban resistance. Economic, education and security themes were selected and data on these themes were examined when this assessment was carried out. Findings from the data concluded that for women to be less affected by urban shocks, their position should be strengthened.